2005
DOI: 10.1007/s11192-005-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction: Conceptual and methodological problems in the ranking of universities by bibliometric methods

Abstract: Ranking of research institutions by bibliometric methods is an improper tool for research performance evaluation, even at the level of large institutions. The problem, however, is not the ranking as such. The indicators used for ranking are often not advanced enough, and this situation is part of the broader problem of the application of insufficiently developed bibliometric indicators used by persons who do not have clear competence and experience in the field of quantitative studies of science. After a brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
335
0
45

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 618 publications
(382 citation statements)
references
References 22 publications
2
335
0
45
Order By: Relevance
“…Em primeiro lugar, muitos já apontaram que contar citações é uma forma falha de avaliar o mérito acadêmico, entre outros porque não se mede a citação a artigos específi-cos [20][21][22][23][24][25] . Em segundo lugar, se um artigo é citado com freqüência como exemplo de pesquisa de má qualidade, mesmo assim a menção repetida a esse artigo irá aumentar o fator de impacto da revista.…”
Section: Discussionunclassified
“…Em primeiro lugar, muitos já apontaram que contar citações é uma forma falha de avaliar o mérito acadêmico, entre outros porque não se mede a citação a artigos específi-cos [20][21][22][23][24][25] . Em segundo lugar, se um artigo é citado com freqüência como exemplo de pesquisa de má qualidade, mesmo assim a menção repetida a esse artigo irá aumentar o fator de impacto da revista.…”
Section: Discussionunclassified
“…Assessment and comparison of journals according to their impact factors is a well-established approach in scientometrics 14,15 , despite the limitations and shortcomings 16 . The impact factor of a journal is defined as the quotient between the number of times an article published in the journal in the previous 2 years is cited in the year of observation and the number of articles this journal has published in these previous 2 years.…”
Section: Methodsologymentioning
confidence: 99%
“…A comprehensive review of problems concerning data quality can be found in (Hood/Wilson 2003). There are several publications which emphasize the aspect of data quality for bibliometric analyses e. g. (Fernández et al 1993;van Raan 2005). I will not expand on the topic of data quality here any further, since it is more a problem of data management than a genuine part of bibliometrics.…”
Section: Related Workmentioning
confidence: 99%